Assessing the Effect of Mental Health Courts on Adult and Juvenile Recidivism: A Meta-Analysis - Fox, Bryanna (American journal of criminal justice, 2021)
Mental health courts (MHCs) are increasingly used across the United States as a means of reducing contact with the criminal justice system for individuals experiencing serious mental health conditions. MHCs rely on diversion from incarceration to rehabilitation, services, and treatment to reduce recidivism and other negative outcomes among individuals with mental health disorders. While MHCs are a potential evidence-based remedy for the intensifying mental health and criminal justice crises in America, there is limited research indicating the overall effects these courts have on recidivism, and whether the effects vary across different sub-groups or research design and analytic features. Therefore, we present a meta-analysis of 38 effect sizes collected from 30 evaluations conducted from 1997 through 2020 on the impact of mental health courts on recidivism for adults and juveniles with mental health issues in the United States. Weighted meta-analytic results indicate that MHC participation corresponds to a 74% decrease in recidivism (OR = 0.26). Notably, the strength of MHC effects are similar for adult and juvenile participants, and stable across varied follow-up periods, study design features, and when prior criminal history, gender and race/ethnicity are controlled for in the analyses. Implications for the criminal justice system are also discussed.